Finite-time convergence robust control of battery energy storage system to mitigate wind power fluctuations. (October 2017) - Deng, Zicong; Xu, Yinliang; Gu, Wei; Fei, Zhongyang
Highlights: The proposed robust control enables flexible time adjustments. A more accurate BESS model is adopted instead of a constant efficiency model. BESS uncertainty and other disturbance are addressed. The SOC regulation enables the BESS ability to smooth the future power fluctuations. Abstract: Wind energy is envisioned to be one of the most promising clean and renewable energy to drive our future society. Due to its intermittency nature, wind power may change rapidly and frequently. Wind power fluctuations pose great challenges on power quality, reliability and raise many other issues like frequency and voltage regulation. This paper proposes a finite-time convergence robust control algorithm of battery energy storage system (BESS) to mitigate the wind power fluctuations. The major advantages of the proposed algorithm include, being insensitive to uncertainty and disturbance, enabling adjustable convergence time to accommodate different operating conditions and maintaining the state of charge (SOC) within a proper range for regulation capability reserve. Finite-time convergence of the proposed algorithm is derived through rigorous analysis. Simulation results demonstrate the effectiveness of the proposed algorithm.